Rancang Bangun Aplikasi Absensi Siswa Pada SD Negeri Weri Kadu Kabupaten Sumba Barat Daya Berbasis Web - Risna Inya Dawa; Elfira Umar; Mitra P. Ayu (GLOBAL SCIENTS PUBLISHER, 2024)
SD Negeri Weri Kadu is one of the agencies engaged in education, where the data processing system carried out is still conventional, one of which is in the student attendance process. The student attendance process has obstacles in terms of collecting attendance data using sheets of paper, causing student attendance data recorded on the sheets to be easily lost, damaged and wasted paper. The purpose of this study is to design a web-based attendance application to make it easier for staff and teachers to carry out the student attendance process. The test method is used the Black box testing method, this method focuses on entering data, system display, memory consumption and data execution speed so that the data entered is not as expected, the system fails. The results of testing the application are admins, teachers and students logging in by entering the username and password to enter the main menu. The admin inputs teacher data, student data, class data, schedule data and subject data, while the teacher carries out the teaching attendance process, sees the schedule and recap of attendance and students carry out the attendance process by choosing the schedule as inputted by the admin. The conclusion of testing the attendance application system is that the input and output functionals go well to change the manual system that has been used so far.